Community evolution and phylogenetic structure of seed plants in Gansu, China - Tian, Qing; Li, Zizhen; Zhou, Xiaolei; Du, Weibo; Song, Lingling; Huang, Rong; Wei, Jia (Frontiers in Plant Science, 2025)
BackgroundUnderstanding plant diversity is essential for revealing how species adapt and evolve across heterogeneous environments.ObjectivesBy integrating phylogenetics and ecology, this study aims to investigate species origins, evolutionary patterns, and biodiversity mechanisms of seed plants in Gansu Province, China. Methods: Using distribution data of seed plants, we analyzed spatial patterns, phylogenetic diversity, community structure, and floristic relationships.ResultsThe seed plant flora of Gansu has diverse temporal origins: 53.85% post-Miocene (0.3–23 Ma), 38.11% Paleogene (23.03–66 Ma), and 8.01% pre-Cretaceous (>66 Ma). The median diversification time is 19.61 Ma; the mean divergence time (MDT) is 28.17 ±25.65 Ma. Species richness (SR) and phylogenetic diversity (PD) are strongly correlated (P < 0.001), both showing a southeast-high to northwest-low pattern. SES-PD reveals phylogenetic overdispersion in 66 counties, suggesting migration corridors, while 14 southeastern counties show clustering due to environmental filtering. NRI and NTI analyses indicate competitive exclusion in 13 counties and environmental filtering in 55.ConclusionThis study highlights the evolutionary complexity and spatial heterogeneity of Gansu’s plant diversity, offering insights into the ecological and historical drivers shaping plant community assembly in arid and montane regions.